2017
DOI: 10.1021/acs.est.7b02397
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Soil Properties and Organic Coating Drive the Phytoavailability of Cerium Oxide Nanoparticles

Abstract: The ISO-standardized RHIZOtest is used here for the first time to decipher how plant species, soil properties, and physical-chemical properties of the nanoparticles and their transformation regulate the phytoavailability of nanoparticles. Two plants, tomato and fescue, were exposed to two soils with contrasted properties: a sandy soil poor in organic matter and a clay soil rich in organic matter, both contaminated with 1, 15, and 50 mg·kg of dissolved Ce(SO), bare and citrate-coated CeO nanoparticles. All the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 45 publications
0
28
0
1
Order By: Relevance
“…In the conclusion, they suggested that model plants should be subjected to tests with NPs of standardized concentrations and sizes. This approach is of particular relevance when risk assessment is to be concerned (Layet et al 2017; Núñez and de la Rosa-Alvarez 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the conclusion, they suggested that model plants should be subjected to tests with NPs of standardized concentrations and sizes. This approach is of particular relevance when risk assessment is to be concerned (Layet et al 2017; Núñez and de la Rosa-Alvarez 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of the RHIZOtest has already been highlighted with CeO 2 NMs. 16 Antagonist clay and carbonate effects on Ag phytoavailability at 100× PEC Fig. 4 shows that for a given modality, Ag fluxes always increased in the order clay < loam with high OM content < sandy loam < loam with high carbonate content (Ag fluxes being significantly lower in the clay soil than in the loam soil with high carbonate content).…”
Section: Resultsmentioning
confidence: 98%
“…The experimental procedure is detailed elsewhere. 16,24 The RHIZOtest is a two-step procedure. The plant seedlings were first grown (preculture period) for 14 days in hydroponics in a cylinder closed at the bottom with a 30 μm polyamide mesh to promote the development of a dense, planar root mat.…”
Section: Rhizotest Experimentsmentioning
confidence: 99%
See 2 more Smart Citations